2020
DOI: 10.1155/2020/8829072
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Blood Parameters and Fecal Microbiota and Metabolites during Pregnant and Lactating Stages in Bama Mini Pigs as a Model

Abstract: This study was conducted to analyze plasma reproductive hormone and biochemical parameter changes, as well as fecal microbiota composition and metabolites in sows, at different pregnancy and lactation stages, using Bama mini pig as an experimental animal model. We found that plasma prolactin (PRL), progesterone, follicle-stimulating hormone (FSH), and estrogen levels decreased from day 45 to day 105 of pregnancy. Plasma total protein and albumin levels were lower in pregnant sows, while glucose, urea nitrogen,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…89 A study showed the changes of fecal microbiota composition and metabolites are related to the plasma reproductive hormones during pregnant and lactating stages in Bama mini pigs model. 90 The SCFA not only regulates the estradiol secretion but also participates in endogenous estrogen receptor-alpha-mediated signaling. 91,92 These result implied that the SCFAs potentially play an important role in DEHP-induced female reproductive toxicology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…89 A study showed the changes of fecal microbiota composition and metabolites are related to the plasma reproductive hormones during pregnant and lactating stages in Bama mini pigs model. 90 The SCFA not only regulates the estradiol secretion but also participates in endogenous estrogen receptor-alpha-mediated signaling. 91,92 These result implied that the SCFAs potentially play an important role in DEHP-induced female reproductive toxicology.…”
Section: Discussionmentioning
confidence: 99%
“…Butyrate plays an important role in improving colonic defense barriers by increasing the expression of tight junction proteins, and the DEHP‐induced increase in the levels of inflammatory factors may be partially due to the reduction in butyrate and subsequent increase in colonocyte permeability 89 . A study showed the changes of fecal microbiota composition and metabolites are related to the plasma reproductive hormones during pregnant and lactating stages in Bama mini pigs model 90 . The SCFA not only regulates the estradiol secretion but also participates in endogenous estrogen receptor‐alpha‐mediated signaling 91,92 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dietary supplementation with Bacillus subtilis C-3102 to sows during gestation and lactation periods and to progeny after weaning modified the fecal microbiota population in sows and nursery piglets ( 13 ). Our previous studies also demonstrated that dietary supplementation with compound probiotics ( L. Plantarum B90 and S. cerevisiae P11 ) or synbiotics (compound probiotics + XOS) during pregnancy and lactation periods can improve piglet's survival and lipid metabolism by altering gut microbiota diversity and composition ( 14 , 15 ). However, the long-term effect of providing probiotics or synbiotics to sows and their offspring on the colonic microbiota, antioxidant capacity, and immune function in weaned piglets is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-established that mammalian gut microbiota regulates host metabolism, and its composition varies in hosts in different physiological states, such as during the pregnancy progression. In addition, maternal physiological changes during pregnancy are highly related to the growth and development of the fetus, which might be influenced by the gut microbiota ( 5 , 6 ). Indeed, maternal gut microbiota (e.g., Firmicutes and Proteobacteria ) could colonize the fetal/neonatal gut during pregnancy (via the placenta) or lactation (via maternal milk and mother's feces) and affecting the offspring's growth and development and as well other physiological functions later in life ( 7 ).…”
Section: Introductionmentioning
confidence: 99%